The Public Accounts and the Education Sector in Portugal: assumption of the legal economy, efficiency and effectiveness - Marques de Almeida, Prof. Doutor J. J.; de Costa Marques, Mestre Maria da Conceição (Education Policy Analysis Archives, 2003)
The National Accounting Plan for the Education Sector (POC - Education) is a Sector Plan for education, which follows on from the approval of the Journal of Public Accounts (OPAP), Decree-Law No. 232/97 of 3 September, the model it is based. With the approval of the POC - Education will create conditions for integrating the accounting, inventory and cost accounting in a modern public as an instrument to support decision-makers and other users of information, to remedy the deficiencies of accounting information previously experienced. As aspects inovadoresdeste plan for the sector, we highlight the cost accounting and the consolidation of accounts. The cost accounting is a mandatory system as an important management tool for analysis and cost control to education, but also the income and results of operations. With the consolidation of accounts is intended to establish a political and management culture group at the same time seeking to facilitate the comparability in time and space, and is also a factor of transparency of public information. Not expected fiscal consolidation, applying the rules only to the consolidation of financial assets.